Colistin nanoparticle assembly by coacervate complexation with polyanionic peptides for treating drug-resistant gram-negative bacteria. (December 2018) - Liu, Yu-Han; Kuo, Shu-Chen; Yao, Bing-Yu; Fang, Zih-Syun; Lee, Yi-Tzu; Chang, Yuan-Chih; Chen, Te-Li; Hu, Che-Ming Jack
Graphical abstract: Abstract: Amidst the ever-rising threat of antibiotics resistance, colistin, a decade-old antibiotic with lingering toxicity concern, is increasingly prescribed to treat many drug-resistant, gram-negative bacteria. With the aim of improving the safety profile while preserving the antimicrobial activity of colistin, a nanoformulation is herein developed through coacervate complexation with polyanionic peptides. Upon controlled mixing of cationic colistin with polyglutamic acids, formation of liquid coacervates was demonstrated. Subsequent stabilization by DSPE-PEG and homogenization through micro-fluidization of the liquid coacervates yielded nanoparticles 8 nm in diameter. In vitro assessment showed that the colistin antimicrobial activity against multiple drug-resistant bacterial strains was retained and, in some cases, enhanced following the nanoparticle assembly. In vivo administration in mice demonstrated improved safety of the colistin nanoparticle, which has a maximal tolerated dose of 12.5 mg/kg compared to 10 mg/kg of free colistin. Upon administration over a 7-day period, colistin nanoparticles also exhibited reduced hepatotoxicity as compared to free colistin. In mouse models of Klebsiella pneumoniae bacteremia and Acinetobacter baumannii pneumonia, treatment with colistin nanoparticles showed equivalent efficacy to free colistin. These results demonstrate coacervation-induced nanoparticle assembly as a promising approach towards improving colistin treatments against bacterial infections. Statement of Significance: Improving the safety of colistin while retaining its antimicrobial activity has been a highly sought-after objective toward enhancing antibacterial treatments. Herein, we demonstrate formation of stabilized colistin nanocomplexes in the presence of anionic polypeptides and DSPE-PEG stabilizer. The nanocomplexes retain colistin's antimicrobial activity while demonstrating improved safety upon in vivo administration. The supramolecular nanoparticle assembly of colistin presents a unique approach towards designing antimicrobial nanoparticles.